PERISTILAHAN MAKANAN TRADISONAL MELAYU NGABANG DI DESA BALAI PELUNTAN KECAMATAN JELIMPO KABUPATEN LANDAK - Rukmana, Imam; Patriantoro, Patriantoro; Sanulita, Henny (Universitas Tanjungpura, 2024)
This research was conducted to find out objectively about the Ngabang Malay Traditional Food Terminology. This research aims to describe an inventory of Traditional Food Terminology in Ngabang Malay. Traditional Food Terminology is studied in the form of terminology, lexical meaning, cultural meaning, and implementation of Indonesian language learning. This study uses adescriptive method in the form of qualitative research. The source of data in this study is the BMDN spoken by the informant in Balai Peluntan Village, Jelimpo District, Landak Regency. The data in this study are traditional foods in BMDN. Data collection techniques used were observation, face-to-face, and note-taking with data collection in the form of lists, notebooks, stationery, gadgets (to record and take pictures), data cards and laptops. Based on the data found 30 data classified based on the form of terminology, namely in the form of monomorphemic and polymorphemic. The results of the classification contained 6 forms of monomorphemic terminology and24 forms of polymorphemic terminology. Based on data analysis, there are 28 traditional food phonemes in BMDN. There are 21 lexical meaning is terms related to cooking from ingredients and spices, and 9 from the way they are served. There are 5 cultural meaning. The learning implementation is in the form of procedure text about culinary terminology.